Modeling and Simulation of Solar Module performance using Five Parameters Model by using Matlab in Baghdad City (Journal of Engineering, 2018)
This work presents the modeling of the electrical response of monocrystalline photovoltaic module by using five parameters model based on manufacture data-sheet of a solar module that measured in stander test conditions (STC) at radiation 1000W/m² and cell temperature 25 . The model takes into account the series and parallel (shunt) resistance of the module. This paper considers the details of Matlab modeling of the solar module by a developed Simulink model using the basic equations, the first approach was to estimate the parameters: photocurrent Iph, saturation current Is, shunt resistance Rsh, series resistance Rs, ideality factor A at stander test condition (STC) by an iteration process. To implement the iteration process, a numerical approach based on the Newton Raphson method has been implemented and programmed in Matlab. The second mathematical model used in Matlab/Simulink using equations for each parameter to determine the parameters at all operating conditions. The Matlab program gives the information about the behavior of the practical PV module, under different atmospheric conditions. The model accuracy was also analyzed through finding out the compatibility between the practical and the theoretical aspects at different solar radiation intensity 500, 750 and 1000 W/m2 by extracting the error ratios. The results show that there is difference between theoretical (modeled) and experimental, the best validation (less error) between five parameters model and experimental maximum power results at radiation 500, 750, 1000 W/m2 and STC was 5.5%, 19%, 18% and 12.3% in January respectively, due to the decreases in ambient temperature and thus decreases in the temperature of solar module in January led to increase in maximum output power and producing best validation between model and experimental in this month.